2022
DOI: 10.1002/aoc.6587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, superoxide dismutase, and antimicrobial activities of Co (II) complexes with Schiff base ligand and their hybrid proteins

Abstract: Metal complexes have been reported to possess excellent free radical scavenging and antimicrobial properties. In the present study, seven linear trinuclear complexes were synthesized based on bis Schiff base ligand and complexes 1, 3–7 are reported for the first time. Their structure was characterized by IR spectroscopy and single crystal diffraction. BSA was used as carrier to hybridize the synthesized complexes to construct hybrid proteins. The interaction between metal complex and BSA was studied by UV–Vis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These compounds can be utilized alone or for the preparation of various hybrid materials, such as, for example, supramolecular elastomers with imine-functionalized polysiloxanes (Hu et al, 2010), conducting metallopolymers for electrochemical sensing (Gonza ´lez et al, 2021), while recently reported co-crystals of a Schiff base with lead iodide perovskite show photo-triggered ferroelectricity (Deng et al, 2022). Furthermore, Schiff base complexes are considered to be an important class of organic compounds with a wide range of biological properties, including free radical scavenging, antibacterial, antitumor activities (Mo et al, 2022). In our laboratory, novel mono-chlorinated Schiff base Cu II complexes have been synthesized and their antibacterial activities tested against Gram-positive and Gram-negative bacteria; the most active were then tested for their antioxidant activities, and as E. coli, in particular, was found to be sensitive to these compounds, their interaction with this bacterium was investigated (Otani et al, 2022).…”
Section: Chemical Contextmentioning
confidence: 99%
“…These compounds can be utilized alone or for the preparation of various hybrid materials, such as, for example, supramolecular elastomers with imine-functionalized polysiloxanes (Hu et al, 2010), conducting metallopolymers for electrochemical sensing (Gonza ´lez et al, 2021), while recently reported co-crystals of a Schiff base with lead iodide perovskite show photo-triggered ferroelectricity (Deng et al, 2022). Furthermore, Schiff base complexes are considered to be an important class of organic compounds with a wide range of biological properties, including free radical scavenging, antibacterial, antitumor activities (Mo et al, 2022). In our laboratory, novel mono-chlorinated Schiff base Cu II complexes have been synthesized and their antibacterial activities tested against Gram-positive and Gram-negative bacteria; the most active were then tested for their antioxidant activities, and as E. coli, in particular, was found to be sensitive to these compounds, their interaction with this bacterium was investigated (Otani et al, 2022).…”
Section: Chemical Contextmentioning
confidence: 99%